2013
DOI: 10.1016/j.ijrobp.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Active Breathing Control in Combination With Ultrasound Imaging: A Feasibility Study of Image Guidance in Stereotactic Body Radiation Therapy of Liver Lesions

Abstract: 3DUS imaging for IGRT of liver lesions is feasible, although using anatomic surrogates in the close vicinity of the lesion may be needed. ABC-based breath-hold in midventilation during 3DUS imaging can reduce the uncertainty of US-based 3D table shift correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Lediju et al extended the use of a robotic US probe for lower abdomen in an animal study and reported that the average 3D reproducibility of their robotic US probe was less than 2 mm [17]. Moreover, the feasibility of implementing US imaging into liver SBRT for eleven patients was shown by Gurp [18]. To our knowledge, this study is the first to investigate and compare the intra-and inter-observer variations between US and CBCT system in kidney cancer.…”
Section: Fargier Et Al Compared the Inter-observer Variations Of Tramentioning
confidence: 86%
“…Lediju et al extended the use of a robotic US probe for lower abdomen in an animal study and reported that the average 3D reproducibility of their robotic US probe was less than 2 mm [17]. Moreover, the feasibility of implementing US imaging into liver SBRT for eleven patients was shown by Gurp [18]. To our knowledge, this study is the first to investigate and compare the intra-and inter-observer variations between US and CBCT system in kidney cancer.…”
Section: Fargier Et Al Compared the Inter-observer Variations Of Tramentioning
confidence: 86%
“…Inverse-planned IMRT is likely to be of benefit in selected patients, especially when delivering a simultaneous integrated boost, and the feasibility of using VBH in these patients needs to be assessed. Finally, breath-holding techniques may be of benefit when treating other tumors, including lung 28 , liver 29 , and gastric 30 cancers. Further work is needed to assess the suitability of using the VBH technique for treating sites other than breast.…”
Section: Discussionmentioning
confidence: 99%
“…Early approaches did include fluoroscopic visualization to quantify diaphragmatic excursion and/or align to implanted metallic fiducials markers [74]. Abdominal compression [4,5,75] and active breath hold [6,76] are two means of minimizing motion associated with respiration, but may be associated with patient discomfort and are affected by patient compliance. The internal target volume (ITV) method strives to account for motion by creating an "envelope" around the tumor volume that encompasses motion of the tumor as visualized on a free-breathing scan [9,10].…”
Section: Motion Managementmentioning
confidence: 99%
“…The ITV approach is practical and easy to employ, but the generation of the ITV can become inaccurate in situations of large tumor motion, and larger volumes of adjacent tissues may receive radiation dose when treating the entire potential extent of tumor motion [77]. Respiratory gating [76,78,79] involves continuously monitoring the respiratory cycle and only treating when the target volume is within a predefined boundary region, constituting only a certain part of the respiratory cycle. Typically, this requires sophisticated imaging capabilities in order to monitor tumor motion and may in fact require fiducial markers, unless the on-board imaging capabilities are accurate enough to allow direct target visualization.…”
Section: Motion Managementmentioning
confidence: 99%